Number Processing and Calculation in Brazilian Children Aged 7-12 Years - Santos, Flávia Heloísa dos [UNESP]; Da Silva, Paulo Adilson; Ribeiro, Fabiana Silva; Ribeiro Pereira Dias, Ana Luiza; Frigerio, Michele Candida; Dellatolas, Georges; von Aster, Michael (Univ Complutense Madrid, Servicio Publicaciones, 2012)
Numerical cognition is based on two components - number processing and calculation. Its development is influenced by biological, cognitive, educational, and cultural factors. The objectives of the present study were to: i) assess number processing and calculation in Brazilian children aged 7-12 years from public schools using the Zareki-R (Battery of neuropsychological tests for number processing and calculation in children, Revised; von Aster & Dellatolas, 2006) in order to obtain normative data for Portuguese speakers; ii) identify how environment, age, and gender influences the development of these mathematical skills; iii) investigate the construct validity of the Zareki-R by the contrast with the Arithmetic subtest of WISC-III. The sample included 172 children, both genders, divided in two groups: urban (N= 119) and rural (N= 53) assessed by the Zareki-R. Rural children presented lower scores in one aspect of number processing; children aged 7-8 years demonstrated an inferior global score than older; boys presented a superior performance in both number processing and calculation. Construct validity of Zareki-R was demonstrated by high to moderate correlations with Arithmetic subtest of WISC-III. The Zareki-R therefore is a suitable instrument to assess the development of mathematical skills, which is influenced by factors such as environment, age, and gender.
Keywords: Zareki-R; mathematical skills; children; neuropsychological assessment; arithmetic